Density of states of interacting two-level systems in amorphous solids in the mean random field approximation - Borisenko, A.A. (Вопросы атомной науки и техники, 2007)
The mean random field approach [1,2] is generalized to the case of random (with certain distribution) values of tunneling matrix elements and double-well potential asymmetries and applied to account for the dipole interaction between two-level systems in glasses. The obtained mean random field distribution function is used to calculate the interaction-modified density of states of the two-level system ensemble. Taking the realistic values of phenomenological parameters, only a minor correction to the low-energy density of states is found. Метод випадкового середнього поля [1, 2] узагальнено для випадкових (з певною функцією розподілу) величин тунельних матричних елементів та асиметрій двоямних потенціалів та застосовано для врахування дипольної взаємодії між дворівневими системами в стеклах. Знайдену функцію розподілу випадкового середнього поля застосовано для розрахунку модифікованої взаємодією щільності станів ансамблю дворівневих систем. При використанні реалістичних величин феноменологічних параметрів знайдена поправка до низькоенергетичної щільності станів є вельми малою. Метод случайного среднего поля [1, 2] обобщен для случайных (с определенной функцией распределения) величин туннельных матричных элементов и асимметрий двухямных потенциалов и применен для учета дипольного взаимодействия между двухуровневыми системами в стеклах. Найденная функция распределения случайного среднего поля использована для расчета модифицированной взаимодействием плотности состояний ансамбля двухуровневых систем. При использовании реалистичных величин феноменологических параметров найденная поправка к низкоэнергетической плотности состояний является весьма малой.